Exploring the Implications of ChatGPT for Language Learning in Higher Education - Baskara, Risang; Mukarto, Mukarto (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
Recent developments in natural language processing have led to the creation of large language models, such as ChatGPT, which could generate human-like text. In this paper, we explore the potential implications of ChatGPT for language learning in higher education. We first provide an overview of ChatGPT and discuss its capabilities and limitations. For instance, ChatGPT can generate coherent and fluent text on various topics but may have difficulties comprehending more complex or abstract ideas. We then consider how ChatGPT could be integrated into language courses and programs in higher education and the potential benefits and challenges of doing so. For example, ChatGPT could provide personalised language instruction or generate authentic language material for learners to engage with. However, using ChatGPT in language learning may also raise concerns about the potential substitution of human language teachers and the ethical implications of using a machine learning system to generate text. Finally, we offer suggestions for future research on using ChatGPT in language learning in higher education, such as studying the effectiveness of ChatGPT-assisted language instruction and exploring the pedagogical implications of using large language models in the language classroom.